Keeping history together: the role of social memory in the nature and functions of news - Kitch, Carolyn (Aurora. Revista de Arte, Mídia e Política, 2011)
Over the past three decades, memory studies have drawn the interest of scholars across the globe and across disciplines, including my own field of journalism. This perspective has provided a seemingly new theoretical lens through which to view news production, content, and audiences. Yet memory always has been implicit in the nature and function of journalism. This essay discusses five ways of understanding present journalism in terms of its uses of the past.